2006
DOI: 10.2165/00019053-200624060-00005
|View full text |Cite
|
Sign up to set email alerts
|

Cost Effectiveness of Enoxaparin as Prophylaxis against Venous Thromboembolic Complications in Acutely Ill Medical Inpatients

Abstract: Results of this evaluation suggest that, in immobilised acutely ill medical inpatients, ENOX may offer hospitals in Germany a very cost-effective option for thromboprophylaxis compared with NPP and a cost-saving alternative compared with LDUFH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 36 publications
0
41
0
Order By: Relevance
“…One assumed that 3% of patients receiving UFH would develop HIT; 13 something we did not observe. At least 3 additional analyses, [14][15][16] all funded by the manufacturer of enoxaparin, assumed that LMWH was both more effective and safer than UFH. We found that adjusted costs were similar or slightly lower with UFH than LMWH.…”
Section: Discussionmentioning
confidence: 99%
“…One assumed that 3% of patients receiving UFH would develop HIT; 13 something we did not observe. At least 3 additional analyses, [14][15][16] all funded by the manufacturer of enoxaparin, assumed that LMWH was both more effective and safer than UFH. We found that adjusted costs were similar or slightly lower with UFH than LMWH.…”
Section: Discussionmentioning
confidence: 99%
“…or t.i.d. for UFH versus once daily), the costs associated with the diagnosis and treatment of heparin-associated thrombocytopenia (HIT) (36,37), and economic analyses performed in Europe, which have demonstrated cost savings from the use of LMWH over UFH that are similar to those found in the United States (38).…”
Section: Efficacy and Safety Of Available Anticoagulantsmentioning
confidence: 97%
“…The IMPROVE study observed that intermittent pneumatic compression was the most common form of VTE prophylaxis utilized in the United States for the medically ill hospitalized patient, although it was used very rarely in other countries (22% vs. 0.2%, respectively) (38). There was variable use of graduated elastic stockings for VTE prophylaxis in the United States and other participating countries (3% vs. 7%, respectively) (38).…”
Section: Mechanical Interventions For Vte Prophylaxis In Medically Ilmentioning
confidence: 99%
See 1 more Smart Citation
“…Active VTE prophylaxis is effective in preventing symptomatic VTE in at-risk hospitalized medical patients with significant reductions in any PE and fatal PE, a nonsignificant reduction in symptomatic DVT, and a nonsignificant increase in major bleeding [7]. As far as pharmocoeconomics is concerned, VTE prophylaxis with low-molecular-weight heparin has been shown to be cost-effective compared with no pharmacological prophylaxis in immobilised acutely ill medical inpatients [8]. However despite the evidence of the benefit of prophylaxis, VTE prophylaxis remains underused [2,9].…”
Section: Introductionmentioning
confidence: 99%